The Abundance Of Sea Cucumber Species In The Waters Of The Wet Laboratory Of East Likupang, North Minahasa - Horman, Christian Andre; Manu, Gaspar D.; Sangari, Joudy R. R. (Jurnal Ilmiah Platax, 2024)
Sea cucumbers, or Holothuroidea, are a class within the Echinodermata phylum. All organisms within this class possess characteristic spiny or knobbed skin composed of calcite particles. Several species of sea cucumber are internationally traded fishing commodities. The hunting of sea cucumbers is not only limited to the high-value species but also extends to lower-value species that initially garnered little attention. The sampling method used in this study began with a daytime location survey, followed by sample collection at night during the lowest tide, using a flashlight for illumination. All species of sea cucumbers found in the surveyed areas were collected. Following the collection, sorting was conducted where only two individuals of each morphological type, color, and other similar traits were kept, while the rest were returned to the waters. The sorted samples were then photographed for identification purposes, and to analyze the density of the discovered sea cucumber species, the number of individuals per suspected species was noted. The images of the collected samples were then compared with a guide for species identification. The World Register of Marine Species (WORMS) 2023 guide was used for this purpose. Subsequently, the number of individual species found was analyzed to determine the density of individuals and the abundance of sea cucumber species. The results of the identification process revealed 7 species with a total of 53 individuals. Keywords: Teripang, Holothuroidea, Likupang Abstrak Teripang atau Holothuroidea merupakan salah satu dari kelas Echinodermata. Semuah golongan organisme ini memiliki ciri kulit yang berduri atau yang berbintil atau tersusun dari sat-sat kapur. Beberapa jenis teripang merupakan komoditi perikanan yang diperdaganngkan secara Internasional. Perburuan teripang tidak saja pada jenis-jenis yang berharga mahal, tetapi juga pada jenis-jenis yang berharga murah yang pada awalnya tidak memiliki perhatian. Metode pengambilan sampel diawali dengan survei lokasi pada siang hari dan pengambilan sampel pada malam hari saat surut terendah dengan menggunakan senter sebagai alat penerang. Spesies yang diambil adalah semua jenis teripang yang ditemukan di perairan tesebut. Setelah teripang terkumpul dilanjutkan dengan penyortiran dimana hanya di ambil dua individu setiap bentuk morfologi, warna dan ciri lainnya yang sama. Sedangkan sisanya dikembalikan ke perairan. Sampel yang telah disortir, lalu difoto untuk keperluan iderntifikasi, kemudian untuk menganalisis kepadatan jenis teripang yang ditemukan dicatat jumlah individu setiap jenis yang điduga merupakan spesies/jenis yang sama. Sampel yang telah diambil foto/gambarnya dicocokkan dengan gambar panduan untuk identifikasi jenis. Panduan untuk mengidentifikasi digunakan WORMS (2023) Selanjutnya jumlah jenis individu yang ditemukan dianalisi untuk mendapatkan kepadatan individu dan kelimpahan spesies teripang. Hasil identifikasi ditemukan 7 spesies dengan jumlah 53 individu. Katakunci: Teripang, Holothuroidea, Likupang.